Interstitial Telomeric Repeats Are Rare in Turtles - Clemente, Lorenzo (Genes (Basel), 2020)
Telomeres are nucleoprotein complexes protecting chromosome ends in most eukaryotic organisms. In addition to chromosome ends, telomeric-like motifs can be accumulated in centromeric, pericentromeric and intermediate (i.e., between centromeres and telomeres) positions as so-called interstitial telomeric repeats (ITRs). We mapped the distribution of (TTAGGG)(n) repeats in the karyotypes of 30 species from nine families of turtles using fluorescence in situ hybridization. All examined species showed the expected terminal topology of telomeric motifs at the edges of chromosomes. We detected ITRs in only five species from three families. Combining our and literature data, we inferred seven independent origins of ITRs among turtles. ITRs occurred in turtles in centromeric positions, often in several chromosomal pairs, in a given species. Their distribution does not correspond directly to interchromosomal rearrangements. Our findings support that centromeres and non-recombining parts of sex chromosomes are very dynamic genomic regions, even in turtles, a group generally thought to be slowly evolving. However, in contrast to squamate reptiles (lizards and snakes), where ITRs were found in more than half of the examined species, and birds, the presence of ITRs is generally rare in turtles, which agrees with the expected low rates of chromosomal rearrangements and rather slow karyotype evolution in this group.